The impact of ash pellet characteristics and pellet processing parameters on ash fusion behaviour - Daley, Patrick James; Williams, Orla; Heng Pang, Cheng; Wu, Tao; Lester, Edward (Elsevier, 2019)
The Ash Fusion Test (AFT) is considered to be the most popular method of characterising the melt characteristics of solid fuel ash. This study shows how pellet preparation can make significant improvements to repeatability. Pelleting pressure, pellet particle size, pellet shape, and furnace ramp rate were investigated to establish the most repeatable representation of ash melting relevant to pulverised fuel combustion in a furnace in an oxidizing atmosphere up to 1600 °C. A 5 mm machine pressed pellet was found to produce the best results as it identified the earliest initial deformation temperature (IDT), gave the least error, and displayed the greatest visible change in pellet height to enable easy identification. Reducing maximum ash particle size to <72 µm and increasing the pressure of the pelleting process was also shown to produce a 120 °C reduction in the IDT when compared with other methods. Reducing the ashing temperature and retaining volatiles lost during high temperature ashing were shown to have a negligible impact on IDT. The characteristic AFT curve was also used to quantify the extent of shrinkage and swelling during the test.